Electrical Injuries in Nepal: An Analysis of Nepal Police Records - Sedain, Bhagabati (Molung Educational Frontier, 2024)
Electric shock is a major cause of injury-related mortality and morbidity. However, it remains a neglected issue in Nepal because mortality and morbidity data are unsystematic and many of them are even unknown. Realizing the need of a systematic study in this regard, I aim to present the available national status of electrical injuries using incidents recorded by Nepal Police from July 2014 to July 2019 for an analysis. The data, obtained in descriptive narratives include information on the injured person's age, sex, place of occurrence, month of occurrence, activity during the occurrence, and the number of casualties per incident. This article explores the issue in some detail to open up the avenues for further study. The findings that I mentioned above indicate a significant burden of electrical injuries in Nepal, potentially higher than reported due to limitations in the police data recording system. As the government regulates electricity distribution, it should also be accountable for preventing electric shock incidents and saving many lives.